2011
DOI: 10.1111/j.1524-4725.2011.02065.x
|View full text |Cite
|
Sign up to set email alerts
|

Periorbital Hyperpigmentation in Asians: An Epidemiologic Study and a Proposed Classification

Abstract: The vascular form of POH was the predominant type. We propose a comprehensive classification for POH that we hope will influence the choice of treatment modalities used in managing POH in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 15 publications
11
96
5
1
Order By: Relevance
“…42.3% cases had a positive family history,but the finding was not statistically significant. This was also highlighted in the study by Ranu et al 11 . Melasma was exclusively seen in females in the study as observed by Bersa et al Among periorbital infections, viral infections outnumbered bacterial infections.…”
Section: Periorbital Miscellaneous Disorderssupporting
confidence: 66%
“…42.3% cases had a positive family history,but the finding was not statistically significant. This was also highlighted in the study by Ranu et al 11 . Melasma was exclusively seen in females in the study as observed by Bersa et al Among periorbital infections, viral infections outnumbered bacterial infections.…”
Section: Periorbital Miscellaneous Disorderssupporting
confidence: 66%
“…The available treatment options for POM include topical depigmenting agents, such as hydroquinone, kojic acid, azelaic acid, topical retinoic acid and physical therapies, including chemical peels, surgical corrections, and laser therapy, most of which were already tried scientifically for melisma and found to be successful. 13,14 There is scarcity of data regarding the incidence and prevalence of periorbital melanosis due to its transitory nature and lack of reasonable etiological explanation. In anrecent Indian study, it was found that POH was most prevalent in the age group of 16 to 25 years and it is more common among females.…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, melanosome degradation within the keratinocyte is slower in darkly pigmented skin when compared with lighter skin types. 15 The melanin content and melanosomal dispersion pattern is thought to confer protection from damage induced by UV radiation. 3,16 Kaidbey et al 16 demonstrated that black epidermis, on average, provides a sunprotection factor (SPF) of 13Á4.…”
Section: Discussionmentioning
confidence: 99%
“…20,22 ICHOR is characterized by bilateral darkening of the orbital skin and eyelid, which is not secondary to systemic or local disease. 20 In a study by Ranu et al 15 on 200 patients with periorbital hyperpigmentation, possible causes were delineated according to history, physical examination and assessment by dermatologists measuring with a Mexameter â (Courage-Khazaka Electronics, Cologne, Germany). They found the commonest forms to be the vascular type (41Á8%) characterized by the presence of erythema involving inner aspects of lower eyelids with prominent capillaries/telangiectasia or presence of bluish discoloration due to visible blue veins; constitutional form (38Á6%) characterized by the presence of brown-black hyperpigmentation of the lower eyelid skin along the shape of orbital rim; PIH (12%); and shadow effects (11Á4%) due to an overhanging tarsal muscle or deep tear trough.…”
Section: Periorbital Hyperpigmentationmentioning
confidence: 99%